Intravitreal dexamethasone implant Ozurdex in the treatment of diabetic macular edema in patients not previously treated with any intravitreal drug: a prospective 12-month follow-up study. (2nd December 2019) - Menezo, Marc; Roca, Manuel; Menezo, Víctor; Pascual, Isabel
Abstract: Objective: To evaluate the mid-long-term efficacy and safety of the dexamethasone intravitreal (DEX) implant (Ozurdex 1 ) in naïve patients with diabetic macular edema (DME). Methods: Prospective and single-center study conducted on consecutive patients with a diagnosis of DME, who received a DEX implant and were followed up for at least 12 months. The main outcomes measurements were the mean change in best corrected visual acuity (BCVA) and in foveal thickness (FT) as compared to the baseline values. Results: Of the 84 screened patients 50 were included in the study. The BCVA significantly improved from 52.4 (20.4) letters at baseline to 62.6 (15.6), 61.2 (18.4), 61.6 (18.6), 60.6 (19.0), and 60.6 (18.8) at 2, 4, 6, 12 months and end of follow-up period, respectively (repeated measures ANOVA and the Greenhouse-Geisser correction; p = .0008). At the end of the follow-up period, a gain of BCVA of ≥5, ≥10, and ≥15 letters were observed in 26 (52.0%), 18 (36.0%), and 16 (32.0%) patients, respectively. The mean FT was significantly reduced from 446.0 (139.9) µm at baseline to 327.2 (103.6) at the end of follow-up (repeated measures ANOVA and the Greenhouse-Geisser correction; p = .0008). During the study follow-up, the patients receive a mean of 3.4 (2.9–3.9) implants. Of the 32 phakic eyes at baseline, 17 (53.1%) either developed new lens opacity or progression of an existing opacity. Conclusion: In eyes with DME not previously treated with intravitreal drugs, DEX implants provide meaningful functional and anatomical benefits, and these results are sustained mid–long-term.